Estresse metabólico em bovinos: efeito em gametas e células foliculares - Missio, Daniele (2022)
The fertility of dairy cows has declined in recent years and the metabolic disturbances that occur during the transition period have contributed to lower reproductive performance. During the period of negative energy balance (NEB), there is an increase in plasma concentrations of non-esterified fatty acids (NEFA) and ketone bodies, such as β-hydroxybutyrate (BHBA). Studies have shown that these changes are reflected in the bovine follicular, oviductal and uterine microenvironment. However, the effects of NEFA and BHBA in follicular cells and gametes is not fully elucidated. Therefore, the aim of this thesis was to evaluate the effect of high concentrations of BHBA on gametes, follicular growth, and ovulation in cattle and the effect of using Vitamin E to prevent oxidative stress in blood and follicular fluid of cows in NEB. First, the effects of BHBA on the viability of bovine spermatozoa were investigated. The results showed that high concentrations of BHBA impair the sperm kinetics, without altering the oxidative status and morphology of the cells. Subsequently, we evaluated whether intrafollicular injection (IIF) of BHBA compromises follicular growth and ovulatory cascade as well as steroid production and the abundance of genes related to steroidogenesis, oxidative and endoplasmic reticulum (ER) stress, and apoptosis in granulosa cells. BHBA decreases the diameter of the dominant follicle and the follicular growth rate. However, in this study no harmful effect of BHBA was observed on the ovulatory cascade or on the functionality of granulosa cells. To understand the effects of BHBA on the expansion, oxidative status, and ER stress in bovine cumulus cells and on the rate of nuclear maturation and oocyte cleavage, the third experiment was performed. The results of this study showed that BHBA induces ER stress in cumulus cells up to 12 h of IVM, without compromising the other variables analyzed. To evaluate the effect of parenteral use of vitamin E to prevent oxidative stress in blood and follicular fluid of cows in NEB we performed the last study included in this thesis. The results showed that the concentration of vitamin E in the blood and follicular fluid were higher in cows that received the antioxidant in comparison without Vitamin E. Furthermore, in this study, we can observe that animals that did not receive antioxidant had higher ROS production in the follicular fluid compared to animals treated with 1,000 IU of Vitamin E, demonstrating the effectiveness of the antioxidant. From these data, it was possible to determine that BHBA and NEFA have deleterious effects on gametes and follicular cells and vitamin E, as antioxidant, can minimize these negative effects.